Stacking Sequence Optimization Based on Deflection and Stress using Genetic Algorithms and Finite Difference for Simply Supported Square Laminate Plate Under Uniform Distributed Load - Hade, Nabil H.; Yousuf, Louay Sabah (Nahrain University College of Engineering Journal, 2011)
In this paper, the optimization and increasing of the stiffness of squareplate, numerical simulation of laminate composite plate using genetic algorithms with finite difference analyses, in which applied to the design variables of the objective functions of the stacking sequence are studied. The plates have been evaluated with actual condition of problem such as distributed load,under simply supported boundary condition with different number of layers (5, 10, 20, 30, 50)and different stiffness ratios (E1/E2) 5, 10, 20, 30, 50. The effects of fiber orientation, number of layers and stiffness ratios on the deflection andstress response of symmetric of classical laminated composite plate subjected to uniformly pressure load (flexural loading) are presented. The maximum deflection and stress are the major parameters that were taken into account in the plate design. Then obtain the optimal suitable stacking sequence orientation of composite plate that gives a small maximum deflection and maximum stress of central point of the plate which represent the main aim in this work. Theresults were compared with ANSYS software results and obtain a good agreement